The Tax Obligation and the Payment: Before the Start of Coercive Collection - in the Peruvian Legislation. Notes and Disquisitions - Aguayo López, Juan Maximiliano (2014)
This article presents in general terms the nature and characteristics of some of the key legal institutions of taxation such as tax legal relationship, the principal tax liability and payment as means to cease the obligation (before the actions that can display the State for tax debt collection) and also explaining the most important legal policy issues that such institutions have received in Peru.